Travel and tourism services Zacate's trips travel agency - Pascacio Gómez, Hazel Lisseth; Abarca Valencia, Omairy Jamileth; Domínguez Soltero, Andrea Carolina (Universidad de El Salvador. Facultad de Ciencias y Humanidades, 2025)
Zacate's Trips is a dynamic tour operation designed for both Salvadorans and international travelers eager to discover the captivating beauty of El Salvador. This initiative aims to deliver exceptional tourism experiences through a team of skilled professionals dedicated to enhancing customer satisfaction. Recognizing that modern life often brings stress, Zacate's Trips invites clients to unwind and immerse themselves in a journey filled with joy and tranquility. El Salvador boasts a rich tapestry of attractions, and Zacate's Trips is committed to offering inclusive tours that cater to families, ensuring that everyone can participate in the adventure together. The project integrates activities that promote awareness and sustainability, striving to mitigate ecological impacts. In essence, Zacate's Trips guarantees an unparalleled and comprehensive experience for all participants, whether they are local residents or visitors, fostering a deeper connection to the natural world and the cultural richness of El Salvador